Framework for Implementing Temporal Big Data Analytics in Organizations - Maria MACH-KRÓL (Communications of International Proceedings, 2021)
The research objective for this study is to develop the framework for implementing temporal big data analytics (TBDA) in organizations. The need for a temporal framework is identified. Existing implementation frameworks for big data are presented. Requirements for temporal big data implementation are shown. Finally, the framework for temporal big data analytics adoption in organization is presented. The study is based mainly on the results of our previous research, a critical analysis of literature, and creative thinking. The results of this research can be used by IT, business leaders, and policy makers as they plan and develop temporal big data analytics in their organizations. The paper provides valuable information on temporal big data implementation issues in organizations.
Keywords: Temporal big data analytics; implementation; leagile approach; DSDM; Scrum.